Transdermal buprenorphine for in-hospital transition from full agonist opioids to sublingual buprenorphine: a retrospective observational cohort study. (3rd June 2022) - Baumgartner, Kevin; Salmo, Ellen; Liss, David; Devgun, Jason; Mullins, Michael; Galati, Bridget; Kelly, Jeannie; Schwarz, Evan
Abstract: Introduction: Patients with opioid use disorder may have difficulty transitioning from full-agonist opioids to sublingual buprenorphine due to the risk of precipitated opioid withdrawal. Novel strategies have been developed to facilitate this transition, including the use of micro-dosing with transdermal buprenorphine. We began using a transdermal buprenorphine transition strategy at our hospital in 2019. Methods: We performed a retrospective observational cohort study of patients treated with transdermal buprenorphine to facilitate transition from full-agonist opioids (prescribed or recreational) while hospitalized between January 2019 and December 2020. Patients were excluded if transdermal buprenorphine was given for pain, if they did not receive at least one dose of sublingual buprenorphine while hospitalized, or if their clinical course precluded analysis of their tolerance of the transition protocol. Data on the doses and timing of medications, symptoms during transition, and hospital outcomes were abstracted from the electronic medical record. Results: We identified 41 cases that satisfied inclusion and exclusion criteria. Thirty-five cases involved a transition from medically indicated opioids; of these, 8 cases involved a transition from methadone. Six cases involved a transition from illicit opioids used prior to hospital presentation. For patient transitioning from medically indicated opioids, the median milligram morphine equivalent (MME) on the day prior to transdermal buprenorphine application was 63.8 (range 0-900, IQR 153.8) and the median MME on the day of transdermal buprenorphine application was 34.5 (range 0-600, IQR 65.3). The median initial dose of sublingual buprenorphine administered was 8 mg (range 2-8mg, IQR 6mg), the median total first-day dose was 16mg (range 2-24mg, IQR 16mg), and the median total daily dose on the last day of follow-up was 16mg (range 2-24mg, IQR 16mg). In 38 cases, patients completed the transition to sublingual buprenorphine and were still taking buprenorphine at the time they left the hospital. The transition protocol was fairly well-tolerated, with 59% of cases tolerating it well and 32% tolerating it fairly. Discussion: Our findings suggest that the use of transdermal buprenorphine to facilitate transition to sublingual buprenorphine is generally well-tolerated, and may be helpful in hospitalized patients. We identified several areas for improvement in future practice by reviewing the clinical courses of patients who tolerated transition poorly. Limitations of the study include its retrospective chart review design, the lack of a standardized transition protocol during the study period, and the lack of standardized data in the medical record regarding patients' tolerance of the transition protocol. Future research should include prospective studies using a standardized protocol and structured, pre-planned assessments of opioid withdrawal during the transition period. Conclusion: The use of transdermal buprenorphine to facilitate induction of sublingual buprenorphine therapy in hospitalized patients with OUD was generally well-tolerated in this single-center retrospective observational study. Further prospective research is needed to demonstrate efficacy and optimize treatment protocols.